Comparative studies: teaching activities in technical universities between engineering and non-engineering educators in Malaysia - Tee, Tze Kiong; Alias, Maizam; Ming Foong, Ming Foong; Mohamad, Mimi Mohaffyza; Sukardi, Sukardi (Research Article, 2021)
Education in general and teachers in particular play a very important role in meeting the demands of the 21st century and, with the rapid advancement of technology, teachers face greater challenges in choosing teaching methods for optimal learning, which include considerations of the learning environment, the context of students and the content of learning. Educators who involved in Technical and Vocational Education and Training (TVET) must properly prepare their students to live and work in the 21st Century. This preparation includes providing themselves to apply the solid knowledge and skills by developing instruction based on contemporary educational thinking and practices. The aim of this study was to generate empirical evidence on the differences in the teaching activities used by educators in technical universities for developing 4C skills. A hundred of each engineering and non-engineering educators from Malaysia were surveyed on the teaching activities that they used to promote 4C skills among their students. The results have shown that there were similarities and differences of the method used by the teachers The 4Cs learning activity instrument was used to gather data on activities sued by teachers for developing critical thinking, communication, collaboration and creativity. The findings have shown that the methods used by the educators varied depending on backgrounds of the educators. In general, engineering educators tend to be different in their teaching activities between non engineering educators. The findings have created a better understanding on how educators may differentiate their activities according to background which could be useful knowledge for future inter-programmed and inter-country collaborations